2005
DOI: 10.1089/jam.2005.18.294
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of an Erythropoietin-Fc Fusion Protein by Inhalation in Humans through an Immunoglobulin Transport Pathway

Abstract: A novel drug delivery platform has been developed that utilizes a naturally occurring receptor known as the neonatal Fc receptor (FcRn). The receptor is specific for the Fc fragment of IgG and is expressed in epithelial cells where it functions to transport immunoglobulins across these cell barriers. It has been shown that FcRn is expressed in both the upper and central airways in non-human primates as well as in humans. Pulmonary delivery of an erythropoietin- Fc fusion molecule (EpoFc) was previously demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 24 publications
2
87
1
2
Order By: Relevance
“…20 Delivery of erythropoietin-Fc (EpoFc) fusion protein by inhalation in a human Phase 1 clinical study showed »70% of the Epo-Fc was delivered safely and effectively to the central lung region. 21 Furthermore, a mouse FcRn-incorporated PBPK model predicted that the skin could account for 33% of the total IgG elimination. 6 Our data support this prediction by taking into account that skin takes a large percentage of body weight.…”
mentioning
confidence: 99%
“…20 Delivery of erythropoietin-Fc (EpoFc) fusion protein by inhalation in a human Phase 1 clinical study showed »70% of the Epo-Fc was delivered safely and effectively to the central lung region. 21 Furthermore, a mouse FcRn-incorporated PBPK model predicted that the skin could account for 33% of the total IgG elimination. 6 Our data support this prediction by taking into account that skin takes a large percentage of body weight.…”
mentioning
confidence: 99%
“…Transepithelial transport in the lung using monomeric erythropoietin-Fc fusion protein (a single erythropoietin protein fused with Fc dimer) is effective and safe in human trials with 70% deposition of aerosolized doses. 62,72 In a different configuration of Fc fusion with follicular stimulating hormone (FSH), which is composed of α and β subunits, both the single chain and the heterodimer FSH-Fc fusion proteins were successfully delivered to the circulation via oral and pulmonary administration in rats and cynomolgus monkeys. Immunization.…”
mentioning
confidence: 99%
“…A few small-scale clinical trials have been conducted on inhalation of other systemicallyacting therapeutic proteins, including interferon alpha-2b (19.3 kDa), human growth hormone (22 kDa) (Walvoord et al, 2009), an erythropoietin-Fc fusion protein (112 kDa) (Dumont et al, 2005). Inhalation of growth hormone is a potential alternative to growth hormone injection, which could offer improved patient adherence especially in pediatric patients.…”
Section: Fig 1 Factors Affecting Pulmonary Deliverymentioning
confidence: 99%
“…Although children preferred the inhalation route of therapy, ongoing development of growth hormone inhalation has been delayed due to its low bioavailability. An erythropoietin-Fc fusion protein was absorbed in www.intechopen.com the bloodstream following delivery to the central lung regions in humans, with a dosedependent concentrations in the serum, suggesting that large therapeutic molecules can be delivered to humans via the lungs using the FcRn-mediated transport pathway (Dumont et al, 2005).…”
Section: Fig 1 Factors Affecting Pulmonary Deliverymentioning
confidence: 99%